2017
DOI: 10.1016/j.cell.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

SAF-A Regulates Interphase Chromosome Structure through Oligomerization with Chromatin-Associated RNAs

Abstract: SummaryHigher eukaryotic chromosomes are organized into topologically constrained functional domains; however, the molecular mechanisms required to sustain these complex interphase chromatin structures are unknown. A stable matrix underpinning nuclear organization was hypothesized, but the idea was abandoned as more dynamic models of chromatin behavior became prevalent. Here, we report that scaffold attachment factor A (SAF-A), originally identified as a structural nuclear protein, interacts with chromatin-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
254
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(271 citation statements)
references
References 61 publications
17
254
0
Order By: Relevance
“…Indeed, although the compartmentalization was not markedly altered (Fig ) we observed a reduction in TAD boundary strength upon transcriptional inhibition (Fig ). These results are concordant with a model where the act of transcription and or its product influences the nuclear positioning of the newly transcribed DNA locus via interaction with nuclear matrix proteins .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, although the compartmentalization was not markedly altered (Fig ) we observed a reduction in TAD boundary strength upon transcriptional inhibition (Fig ). These results are concordant with a model where the act of transcription and or its product influences the nuclear positioning of the newly transcribed DNA locus via interaction with nuclear matrix proteins .…”
Section: Discussionsupporting
confidence: 87%
“…More recently, active transcription has also been postulated as a major driving force in shaping genome architecture [26][27][28][29]. Not only was it shown that transcriptional elongation can remodel 3D genome structure [30,31], but transcription can also affect TAD interactions [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that R‐loop levels were increased in FANCD2 ‐depleted cells following APH treatment. We also provided evidence for an interaction of FANCD2 with hnRNP U, an RNA‐binding protein that functions in transcription elongation , pre‐mRNA splicing , mRNA stability , and more broadly, interphase chromatin structures . Given the function of hnRNP U in normal RNA metabolism, it is not surprising that hnRNP U function contributes to the regulation of R‐loop levels.…”
Section: Discussionmentioning
confidence: 74%
“…For example, the non-coding RNAs Xist and Firre establish chromatin microarchitectures (Engreitz et al, 2013;Hacisuleyman et al, 2014). Furthermore, chromatin associated RNAs are required for efficient oligomerization of SAF-A protein, which results in decompaction of transcribed euchromatin (Nozawa et al, 2017). The above suggests that transcription as well as RNA have roles in the organization of euchromatin.…”
Section: Introductionmentioning
confidence: 95%